Implementation of An Optical Gauss Meter Based on Ferrite and Hematite Ferrofluids - Lafta, Sadeq H.; Salloom, Hussein T.; Hashim, Furqan S. (Iraqi Journal of Science, 2024)
Three compositions Ni0.5Fe2.5O4, Ni0.7Fe2.3O4, and Fe2O3 were prepared by the co-precipitation method and checked by XDR, SEM, and VSM. The nanoparticles show a good match with the XRD standards. The particle sizes were 25, 32, and 18nm for the above compositions, respectively. The first composition showed the highest magnetization saturation. Suspensions containing the mentioned nanoparticles were prepared with two carrier fluids, distilled water, and dimethylsulphoxide (DMSO). A transmission to ultraviolet-visible light was tested and showed good transparency of more than 60 % in the red light region. The transparency to 623nm laser light under different magnetic fields of the six suspensions was tested. A simple device was fabricated to perform this test. The water suspension in water Ni0.5Fe2.5O4 has a larger variation in the transmitted power. The suspension of hematite shows no sensible change in the transmitted power. The magnetic properties of the nanoparticles and the dispersion property of the carrier fluid were behind the explanation of the suspension behaviors under the influence of the magnetic field.